Investigação de diagramas de coagulação utilizando coagulantes e auxiliares de coagulação de fontes renováveis - Costa, Talita Ferreira de Rezende (2013)
This study investigated the coagulation diagrams using tannin as organic coagulant, from renewable source, associated or not, to the inorganic coagulant aluminium sulphate and to coagulation auxiliaries sodium aluminate (inorganic) and cationic hemicellulose (from renewable source) for treatment of industrial laundry effluent. The methodology consisted of removing oils and greases, followed by filtration, pH adjustment, and application of the coagulants and auxiliaries at various concentrations. Coagulant tannin is mostly effective in removing turbidity in acid pH\'s (3 to 5) when used at concentrations higher than 1000 ppm, possibly acting under the adsorption mechanisms and formation of bridges, and adsorption, and charge neutrality. When associated to sodium aluminate at ratio 3:1 (v/v) tannin, sodium aluminium oxide), it permitted larger removals of turbidity on acid regions for two ranges of concentration (lower than 1500 ppm and higher than 3750 ppm), indicating that the tannin/sodium aluminium oxide interaction is not favourable to undo itself and interact with the effluent particles. The association of tannin with aluminium sulphate presented the largest removals of turbidity at all pH ranges and concentrations investigated, possibly by an interaction between cation Al3+ and the hydroxyls bonded to the tannin benzene ring forming a chelate with more stability and interaction with suspended particles, stabilizing the flocs formed by this interaction. The addition of cationic hemicellulose offers improvements to the removal of turbidity at the basic pH region (worst tannin performance) provided by tannin, however, its action is conditioned to the tannin efficiency in the coagulation process. The possible interactions between the hemicellulose and the effluent suggest interactions of the type hydrogen bridges and dipole-dipole interactions. The use of tannins associated to cationic hemicellulose allows treatment of industrial laundry effluent with formation of sludge of more biodegradability, which is an advantage from the sustainability point-of-view.